De novo mutations in schizophrenia implicate chromatin remodeling and support a genetic overlap with autism and intellectual disability - McCarthy, S E; Gillis, J; Kramer, M; Lihm, J; Yoon, S; Berstein, Y; Mistry, M; Pavlidis, P; Solomon, R; Ghiban, E; Antoniou, E; Kelleher, E; et al. (Molecular psychiatry, 2014)
Schizophrenia is a serious psychiatric disorder with a broadly undiscovered genetic etiology. Recent studies of de novo mutations (DNMs) in schizophrenia and autism have reinforced the hypothesis that rare genetic variation contributes to risk. We carried out exome sequencing on 57 trios with sporadic or familial schizophrenia. In sporadic trios, we observed a ~3.5-fold increase in the proportion of nonsense DNMs (0.101 vs 0.031, empirical P= 0.01, Benjamini–Hochberg-corrected P= 0.044). These mutations were significantly more likely to occur in genes with highly ranked probabilities of haploinsufficiency ( P= 0.0029, corrected P= 0.006). DNMs of potential functional consequence were also found to occur in genes predicted to be less tolerant to rare variation ( P= 2.01 × 10 − 5 , corrected P =2.1 × 10 − 3 ). Genes with DNMs overlapped with genes implicated in autism (for example, AUTS2 , CHD8 and MECP2 ) and intellectual disability (for example, HUWE1 and TRAPPC9 ), supporting a shared genetic etiology between these disorders. Functionally CHD8 , MECP2 and HUWE1 converge on epigenetic regulation of transcription suggesting that this may be an important risk mechanism. Our results were consistent in an analysis of additional exome-based sequencing studies of other neurodevelopmental disorders. These findings suggest that perturbations in genes, which function in the epigenetic regulation of brain development and cognition, could have a central role in the susceptibility to, pathogenesis and treatment of mental disorders.